Digital Financial Assets as a Tool for International Payments - S. N. Ryabukhin; M. A. Minchenkov; I. A. Kokorev; K. L. Meletidi; A. M. Lyukshin (Мир новой экономики, 2024)
The relevance of the research topic is due to the need to develop alternative methods of international settlements for Russia in the context of increasing sanctions pressure. Over the past few years, countries have been actively implementing new tools that have emerged due to digitalization and have been called “digital financial assets”, the potential of which canbe realized, including in the field of international settlements, ensuring a reduction in sanctions pressure on the Russian economy.   The purpose of this article is to identify the possibilities of using digital financial assets as a tool for international settlements.   Methods. The study was carried out using up-to-date data and sources, as well as an analysis of the principles, methodological approaches and practices of using digital financial assets in international settlements.   The scientific novelty of the work is that it presents the mechanism of Russia’s use of digital financial assets for international settlements and highlights its key risks.   The results of the study. The article examines the essence of digital financial assets, reveals the features and mechanisms of their application in international settlements, presents the approaches of various countries toregulate them, and examines the possibilities and risks of their introduction in Russia.   Practical significance. The results and conclusions of the article can be useful both for the scientific community and for participants in foreign economic activity and other organizations working with digital financial assets, as well as for the Bank of Russia.